Validity of alcohol screening instruments in general population gender studies: an analytical review - Oliveira, Janaina Barbosa de [UNESP]; Kerr-Corrêa, Florence [UNESP]; Lima, Maria Cristina Pereira [UNESP]; Bertolote, José Manoel [UNESP]; Santos, Jair Lício Ferreira [UNESP] (Bentham Science Publishers, 2014)
The present study is an analytical review of the methodology used in studies of efficacy of screening instruments to detect harmful use/ alcohol dependence according to the gender in population surveys. Systematic review of bibliography was done, using data from Web of Science, Pubmed and PsycInfo. Population studies were included without date range, in English, Spanish or Portuguese languages, with sample of adults, evaluating psychometric characteristics of any alcohol screening instrument, whereas studies in special population or under treatment as well as prevalence of alcohol consumption were excluded. Thirteen studies were selected to be included in the present review. According to the studies, the instruments that presented a better performance among men were AUDIT and its derivatives (6 studies) and CAGE (2 studies), whereas among women, AUDIT and its derivatives (7 studies), followed by CAGE (3 studies). The increase of consumption and problems related to alcohol use and its implications for public health indicate the need and urgency for adequacy of screening instruments to differences of gender in general population. The population surveys in the area are scarce. Furthermore, the found studies present heterogeneous methodology which makes accurate comparisons difficult.
Keywords: Ethanol; Gender; General population; Instruments; Review; Screening